2021
DOI: 10.1063/5.0067355
|View full text |Cite
|
Sign up to set email alerts
|

A single spectroscopic probe for in situ analysis of electronic and vibrational information at both sides of electrode/electrolyte interfaces using surface-enhanced Raman scattering

Abstract: Surface-enhanced Raman scattering (SERS) at electrode/electrolyte interfaces includes inelastic light scattering not only by molecular vibrations in the electrolyte phase but also by conduction electrons in the metal electrode phase. While the former, i.e., vibrational SERS (VSERS), is widely used to obtain chemical information on electrode surfaces, the latter, i.e., electronic SERS (ESERS), is still under discussion as a possible origin of the SERS background. Given that electronic Raman scattering is essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The respective potentials of zero charge (pzc) for the different solution/Au interfaces were determined by measuring the double-layer capacities at the SERS-active Au surfaces. 29 SERS spectra were recorded using a home-built inverted microscope Raman system with an objective (40×, 0.6 N.A.). 28 A He-Ne laser radiation of 632.8 nm was further monochromatized using an ultra-narrow band laser-line lter with a bandwidth of less than 0.4 nm FWHM (reecting volume Bragg grating (VBG) line lter, OptiGrate Corp).…”
Section: Electrochemical and Spectroscopic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The respective potentials of zero charge (pzc) for the different solution/Au interfaces were determined by measuring the double-layer capacities at the SERS-active Au surfaces. 29 SERS spectra were recorded using a home-built inverted microscope Raman system with an objective (40×, 0.6 N.A.). 28 A He-Ne laser radiation of 632.8 nm was further monochromatized using an ultra-narrow band laser-line lter with a bandwidth of less than 0.4 nm FWHM (reecting volume Bragg grating (VBG) line lter, OptiGrate Corp).…”
Section: Electrochemical and Spectroscopic Measurementsmentioning
confidence: 99%
“…However, THz responses in SERS spectra are invariably concealed by a large spectral background generated from plasmonic metal surfaces, which is problematic in analysing THz-vibrations. 28,29 Time-domain Raman spectroscopy may be one of the options to obtain THz-vibrations without the use of plasmon resonances. 30,31 However, there is a serious drawback of this technique to obtain one spectrum for the THz region in real time.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency-extended SERS: signal detection SERS spectra for SAM-covered Au surfaces were measured using a home-built inverted microscope Raman system with an objective (40×, 0.6 N.A.). 16,[21][22][23][24] A He-Ne laser radiation of 632.8 nm was filtered using an ultra-narrowband laser-line filter (reflecting volume Bragg grating, OptiGrate Corp). The backscattered Raman signals from the sample were monitored by a CCD-polychromator system (PIXIS 100 BR eX-I or PIXIS 400BR & IsoPlane, Princeton Instruments) after Rayleigh scattering light was removed by ultra-narrowband notch filters (reflecting volume Bragg grating, OptiGrate Corp).…”
Section: Preparation Of Thiol-covered Au Surfacesmentioning
confidence: 99%
“…16 Recently, the origin of the SERS background has been ascribed to plasmon-enhanced electronic Raman scattering in the conduction band of metal substrate, meaning that the steep increase of the background intensity in the low-frequency region is caused by thermal occupation of the photon states. [17][18][19][20][21][22][23] Based on this mechanism, a practical method to extract vibrational information from measured SERS spectra has been developed, which enables us to perform vibrational analysis of SERS spectra in the low-frequency region more accurately. 24 Herein, we experimentally demonstrate that low-frequency SERS spectroscopy can be utilized as an alternative to in situ molecular mass spectrometry at a buried interface by measuring frequencies of surface-adsorbate vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…These additional effects influence the material type, morphology, charge density, and permittivity at the nanostructured metal–liquid interface, directly or indirectly affecting both the PE-VRS and the background emission processes. While several studies have shown a correlation between voltage and plasmon-enhanced metal luminescence within electrochemical setups, a comprehensive understanding of the connection between electrode interfacial behavior and the microscopic representation of plasmon-enhanced metal luminescence remains elusive. Furthermore, most EC-SERS studies have employed nonuniform plasmonic devices based on metal nanoparticle aggregates or roughened metal electrodes with randomly distributed or mechanically unstable plasmonic hotspots, ,, , limiting EC-SERS measurement reproducibility for reliable analysis of voltage-dependent spectral background information.…”
Section: Introductionmentioning
confidence: 99%